2014
DOI: 10.4103/0255-0857.142241
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of scrub typhus in fever of unknown origin (FUO) cases: An experience from Rajasthan

Abstract: The present study emphasises the importance of scrub typhus among cases of FUO especially after rainy season and during early cooler months. The study also highlights the significance of ELISA method for rapid and early reporting and ruling out scrub typhus in FUO cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 14 publications
11
12
0
Order By: Relevance
“…Scrub typhus positivity was significantly higher among women, 314 (35.9%) compared with men, 210 (22.8%) with the ratio of 1.5:1. Likewise, Bithu et al, 22 Vivekanandan et al 23 and Saleem et al 24 also found female preponderance in their study. In contrast, Jyothi et al 25 and Medhi et al 26 found that prevalence rate for scrub typhus was higher among men.…”
Section: Correlation Between Elisa and Weil-felix Testsupporting
confidence: 55%
“…Scrub typhus positivity was significantly higher among women, 314 (35.9%) compared with men, 210 (22.8%) with the ratio of 1.5:1. Likewise, Bithu et al, 22 Vivekanandan et al 23 and Saleem et al 24 also found female preponderance in their study. In contrast, Jyothi et al 25 and Medhi et al 26 found that prevalence rate for scrub typhus was higher among men.…”
Section: Correlation Between Elisa and Weil-felix Testsupporting
confidence: 55%
“…The study by Bithu et al, in their study reported that out of 133 infected with Scrub typhus, 80 (62%) were females and 53 (37.3%) males. 28 Vivekanandan M et al, also found female prepordance in their study. 29 Scrub typhus positivity was significantly higher among females as compared to males.…”
Section: 27supporting
confidence: 51%
“…The results were similar to other studies that found dengue was responsible for febrile illnesses in sub-Saharan Africa and other countries [8][9][10]. A study in Rajasthan, India [11] presented 49.1% of patients with FUO that were confirmed by scrub typhus immunoglobulin M antibodies by ELISA and had a similar result to another prospective study among patients with FUO in Chennai City, South India [12], presenting 23% of patients positive for immunoglobulin M antibodies against Orientia tsutsugamushi. FUO is one of the diseases notified by law under the National Communicable Disease Surveillance System in Thailand.…”
Section: Discussionsupporting
confidence: 89%